Impacts of a novel defensive symbiosis on the nematode host microbiome - Dahan, D; Preston, G; Sealey, J; King, K (BMC, 2020)
Background: Bacteria adapted to live within animals can protect their hosts against harmful infections. Beyond antagonism with pathogens, a ‘defensive’ bacterial symbiont could engage in additional interactions with other colonizing micro-organisms. A single bacterium might thus have cascading ecological impacts on the whole microbiome that are rarely investigated. Here, we assess the role of a defensive symbiont as a driver of host-associated microbiota composition by using a bacterial species (Enterococcus faecalis) that was previously experimentally adapted (Enterococcus faecalis) to a nematode host model (Caenorhabditis elegans).